Effect of Workload and Work Environment on Job Satisfaction of Employees at PT ABC - Handika Eka Pratama; Rizal Ramdan Padmakusumah (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to examine the effect of workload and work environment on employee job satisfaction at PT ABC. The research is important as increasing workload demands and working conditions may influence employee attitudes and organizational sustainability. Methodology: This research employs a quantitative approach using a survey method. Data were collected from 45 employees using structured questionnaires and analyzed using descriptive statistics and multiple linear regression analysis. Classical assumption tests were conducted to ensure the validity of the regression model. Results: The results indicate that workload and work environment have a positive and significant effect on job satisfaction, both partially and simultaneously. The work environment shows a stronger influence compared to workload. Findings: The findings reveal that workload perceived as manageable and supported by a conducive work environment contributes to higher employee job satisfaction. Novelty & Originality: This study provides empirical evidence that workload can function as a positive determinant of job satisfaction when aligned with employee capacity and supported by a supportive work environment, particularly in the context of a technical service company. Conclusions: The study concludes that an integrated management of workload and work environment is essential to enhance employee job satisfaction and organizational effectiveness. Type of Paper: This paper is a research article.